2022
DOI: 10.1111/os.13232
|View full text |Cite
|
Sign up to set email alerts
|

Role of Exosomal miR‐223 in Chronic Skeletal Muscle Inflammation

Abstract: As skeletal muscle is one of the largest organs in the body, its damage can directly reflect a decline in somatic function, thus, further affecting daily life and health. Inflammation is a prerequisite for the repair of injured skeletal muscles. Chronic inflammation induced by inadequate repair in skeletal muscle aggravates tissue injury. Exosomes regulate inflammatory responses to facilitate the repair of skeletal muscle injury. Moreover, exosomal miR‐223 with high specificity is the most abundant miRNA in pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 96 publications
(115 reference statements)
0
4
0
Order By: Relevance
“…EVs offer a promising avenue to indirectly guide the repair of skeletal muscle tissue in many cases.Engineered EVs can be customized with specific cargos, including growth factors, microRNAs, or proteins, known to stimulate myogenic activity [275]. These bioactive payloads have the potential to promote satellite cell activation, muscle cell differentiation, and overall tissue repair [276][277][278]. For instance, previous studies have demonstrated that myomiRs like miR-206, miR-133a, and miR-1 play crucial roles in myoblast proliferation [279].…”
Section: Skeletal Muscle Repairmentioning
confidence: 99%
See 1 more Smart Citation
“…EVs offer a promising avenue to indirectly guide the repair of skeletal muscle tissue in many cases.Engineered EVs can be customized with specific cargos, including growth factors, microRNAs, or proteins, known to stimulate myogenic activity [275]. These bioactive payloads have the potential to promote satellite cell activation, muscle cell differentiation, and overall tissue repair [276][277][278]. For instance, previous studies have demonstrated that myomiRs like miR-206, miR-133a, and miR-1 play crucial roles in myoblast proliferation [279].…”
Section: Skeletal Muscle Repairmentioning
confidence: 99%
“…Additionally, in case of chronic inflammation followed by skeletal muscle injury, EV miR-223, the most abundant miRNA in peripheral blood, has been implicated in modulating the inflammatory response to skeletal muscle damage [280][281][282][283]. Studies have demonstrated that miR-223 down-regulates the expression of TNF-α and other pro-inflammatory molecules, inhibits inflammatory cell infiltration, and decreases the extent of necrotic muscle tissue [278,284]. Consequently, miR-223 holds promise as a potential biomarker and therapeutic target for addressing chronic inflammation associated with inadequate muscle regeneration and repair following injury.…”
Section: Skeletal Muscle Repairmentioning
confidence: 99%
“…Current research focuses on mesenchymal stem cells, which are considered the "bank" of regenerative medicine due to their ability to evade the immune system, selfregenerate, and differentiate into various cell types with greater specificity than differentiated cells. [68][69][70] However, safety concerns have been raised regarding stem cell therapy, including ethical issues and the risk of teratoma formation with embryonic stem cell therapy, genomic instability and tumorigenesis with pluripotent stem cell therapy, and promoting tumor growth, metastasis, and differentiation into non-target tissues with mesenchymal stem cell therapy. [71][72][73][74][75] Encouragingly, recent evidence suggests that stem cells may exhibit beneficial effects through the EVs they release, playing a role similar to stem cells in tissue regeneration and damage repair.…”
Section: Evs As Drug or Target In Therapeutic Applicationmentioning
confidence: 99%
“…Additionally, apoptotic and necrotic effects initiated by TNF-α during skeletal muscle injury negatively affect the contractile properties of the injured muscle [ 4 ]. Long-term release of TNF-α continuously activates the NF-κB signaling cascade, which forms a vicious cycle that results in a chronic inflammation [ 5 ].…”
Section: Introductionmentioning
confidence: 99%